Crisaborole Ointment Improves Quality of Life of Patients with Mild to Moderate Atopic Dermatitis and Their Families - Eric L. Simpson; Amy S. Paller; Mark Boguniewicz; Lawrence F. Eichenfield; Steven R. Feldman; Jonathan I. Silverberg; Sarah L. Chamlin; Lee T. Zane (Adis, Springer Healthcare, 2018)
Abstract Introduction The impact of crisaborole ointment, a nonsteroidal phosphodiesterase 4 inhibitor for the treatment of mild to moderate atopic dermatitis (AD), on quality of life (QoL) was assessed in two identically designed phase 3 studies (AD-301: NCT02118766; AD-302: NCT02118792, both at http://www.clinicaltrials.gov). Methods In both studies, patients aged ≥ 2 years with mild to moderate AD per the Investigator's Static Global Assessment were randomly assigned 2:1 to receive crisaborole or vehicle twice daily for 28 days. QoL was assessed using the Children's Dermatology Life Quality Index (CDLQI) (2-15 years), the Dermatology Life Quality Index (DLQI) (≥ 16 years), and the Dermatitis Family Impact Questionnaire (DFI) (parents/caregivers/family of patients aged 2-17 years). Established QoL score severity bands provided clinical context. Results Greater mean improvement in QoL was observed in crisaborole-treated patients than in vehicle-treated patients at day 29 [mean change from baseline (∆BL), CDLQI: − 4.6 vs. − 3.0; P < 0.001; DLQI: − 5.2 vs. − 3.5; P = 0.015]. At baseline, more than half the patients had a "moderate effect" or higher of AD on QoL. At day 29, there was a trend toward more crisaborole- than vehicle-treated patients having "small effect" to "no effect", The QoL of parents/caregivers/family improved more for crisaborole-treated than for vehicle-treated patients (∆BL, DFI: − 3.7 vs. − 2.7; P = 0.003). Conclusion Crisaborole treatment results in clinically meaningful improvement in QoL for patients and their parents/caregivers/families. Trial Registration AD-301: http://www.clinicaltrials.gov, NCT02118766; AD-302: http://www.clinicaltrials.gov, NCT02118792. Funding Anacor Pharmaceuticals, Inc., a wholly owned subsidiary of Pfizer Inc., New York, NY.